STEP Parenting: A Review of the Research - Robinson, Paul W.; Robinson, Michael P. W.; Dunn, Todd W. (Canadian Journal of Counselling and Psychotherapy, 2007)
In response to Dinkmeyer, McKay, and Dinkmeyer Jr.'s (1990) claim that individuals were incorrectly reporting Systematic Training for Effective Parenting (STEP) as being ineffective and recent claims of STEP being ineffective (e.g., Taylor & Biglan, 1998), the purpose of this article was to review the research and statements made about STEP's effectiveness. This review looked at the issue of STEP being effective from several research perspectives and concluded Dinkmeyer et al.'s claims of STEP being effective were not supported by the research. Additional suggestions for improving practitioner's acceptance of parenting systems and procedures with scientific validation are also included.